2016
DOI: 10.1097/md.0000000000002796
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and Subcutaneous Metastases From Atypical Laryngeal Carcinoids

Abstract: The incidence of cutaneous and subcutaneous metastases from atypical laryngeal carcinoids is approximately 20%. However, the pathogenesis and natural history of, and prognostic factors for, the condition remain poorly understood. We reported a 54-year-old female presented with cutaneous and subcutaneous metastases from atypical laryngeal carcinoid. Laryngoscopy revealed a 0.5 × 1.5-cm reddish mass on the laryngeal surface of the epiglottis. Under general anesthesia, a biopsy sample was obtained via suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Wang et al reviewed 48 reported cases of atypical laryngeal carcinoids diagnosed since 2005 and observed that cutaneous metastasis occurred in 22% of patients. Patients were typically male smokers who presented with dysphagia and tumor located in the supraglottis . As laryngeal LCNECs were formerly grouped with atypical laryngeal carcinoids, it is possible that some of the cases metastasizing to the skin in their series would meet current diagnostic criteria of LCNEC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reviewed 48 reported cases of atypical laryngeal carcinoids diagnosed since 2005 and observed that cutaneous metastasis occurred in 22% of patients. Patients were typically male smokers who presented with dysphagia and tumor located in the supraglottis . As laryngeal LCNECs were formerly grouped with atypical laryngeal carcinoids, it is possible that some of the cases metastasizing to the skin in their series would meet current diagnostic criteria of LCNEC.…”
Section: Discussionmentioning
confidence: 99%
“…Glut-1, as an important carrier of glucose uptake and a major protein involved in the transport of glucose, plays a key role in maintaining the homeostasis of the body [9]. It has been reported that Glut-1 transporters are expressed at higher levels in human solid cancer cells compared to their normal counterparts [10][11][12]. Glut-1 also affects cell proliferation and chemoradiotherapy sensitivity of head and neck squamous cell carcinoma, including laryngeal carcinoma13-18.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine carcinoma (NEC) of head and neck is uncommon 15. NEC is an aggressive malignant tumor that most commonly affects the larynx 6.…”
Section: Introductionmentioning
confidence: 99%